KOMUNIKASI STUNTING : STRATEGI DAN AKSI STUDI KASUS DI DESA TRINSING KECAMATAN TEWEH TENGAH KABUPATEN BARITO UTARA - Dharmawan, I Gusti Agung; Gantiano, Hadianto Ego; Edung, Tardi; Sutarwan, I Wayan; Suriana, I Ketut (Fakultas Dharma Duta, 2024)
This study examines communication strategies and actions in addressing stunting in Trinsing Village, Teweh Tengah District, North Barito Regency. Considering that the local community strongly adheres to cultural traditions and ancestral beliefs, cultural communication is considered essential as a behavior change approach to prevent stunting. This research employed a descriptive qualitative method through observation, semi-structured in-depth interviews with five key informants, and documentation. Data were analyzed through transcription, reduction, presentation, and conclusion drawing. The findings reveal that local health centers (puskesmas) play a central role in providing stimulus through counseling and consultation, while community health posts (posyandu) contribute to child growth monitoring and nutrition education. Community responses vary, influenced by individual and group characteristics; however, behavior change tends to occur when the stimulus is well received. This study emphasizes the importance of multi-stakeholder collaboration, highlighting behavior change communication strategies as a key approach to raising awareness of child nutrition and health..